Determination of Physicochemical Properties and Oxidative Stability of Rice Bran Oils - Gecgel, Umit; Daglioglu, Orhan; Yilmaz, Ismail; Arici, Muhammet; Guner, Kadir G.; Apaydin, Demet; Dulger, Gizem C.; Ay, Onur; Ersoz, Berna; Cotra, Yosun; Tasan, Murat (UNIV NAMIK KEMAL, 2017)
In this research, it was aimed to determine the effects of stabilization on some physicochemical properties and fatty acid composition of rice bran oil. The rice bran samples (Osmancik and Opela) was stabilized under three ways (microwave, drying oven and microwave + drying oven) including nine conditions (drying oven: 80 degrees C 30 min, 100 degrees C 30 min, 120 degrees C 30 min; microwave : 600 W 1 min, 600 W 2 min, 600 W 3 min; microwave + drying oven: 600 W 2 min microwave -80 degrees C 30 min drying oven, 600 W 2 min microwave -100 degrees C 30 min drying oven, 600 W 2 min microwave -120 degrees C 30 min drying oven). The rice bran oil was obtained by solvent extraction technology. The free fatty acids content, peroxide value, iodine number, saponification number, specific gravity, refractive index, fatty acid composition and the sterol composition of rice bran oil samples were determined. The acidity, peroxide value and iodine number of the oil samples were significantly decreased with the stabilization process applied (p 0,05). beta-sitosterol was detected as the main sterol in rice bran oil.
Keywords: Rice bran oil; oxidative stability; physicochemical properties; stabilization; Agriculture